2016
DOI: 10.1590/18069657rbcs20150198
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Forms in Ultisol Submitted to Burning and Trituration of Vegetation in Eastern Amazon

Abstract: ABSTRACT:The use of fire to prepare agricultural areas is a technique still used by small farmers in eastern Amazon. This type of management changes the dynamics of soil nutrients, especially phosphorus, which constitutes the most limiting nutrient for crop production in tropical soils. This study was carried out to evaluate changes in phosphorus forms in an Argissolo Amarelo Distrófico (Ultisol) submitted to burning and trituration of secondary forest in eastern Amazon. The evaluated systems were: slashand-bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
6
0
1
Order By: Relevance
“…Soils of the Brazilian Cerrado are highly weathered with low natural fertility, high acidity, low cation exchange capacity, low organic matter and high aluminum concentration (Farias et al, 2016). All these factors influence seedling production of some species to a certain extent.…”
Section: Introductionmentioning
confidence: 99%
“…Soils of the Brazilian Cerrado are highly weathered with low natural fertility, high acidity, low cation exchange capacity, low organic matter and high aluminum concentration (Farias et al, 2016). All these factors influence seedling production of some species to a certain extent.…”
Section: Introductionmentioning
confidence: 99%
“…However, chop-and-mulch has not always increased soil carbon stocks (Perrin et al, 2014). A recent study in eastern Amazon that compared the effects of slash-and-burn and chop-and-mulch systems concluded that mulching increases soil phosphorus availability (Farias et al, 2016). However, these authors did not consider that P fertilizer was added to the chop-and-mulch area in the first (Davidson et al, 2008) as well as in the subsequent crop-fallow cycles (O.…”
Section: Introductionmentioning
confidence: 99%
“…Chop-and-mulch areas have to be fertilized to overcome nutrient immobilization after soil tillage (Kato et al, 1999). Thus, the conclusion of Farias et al (2016) is not valid because in their experiment the effects of plant strategies to acquire P could not be separated from the contribution of fertilizer-P. In fact, further investigation is needed to understand the effects of chop-and-mulch systems on P cycling in the eastern Amazon.…”
Section: Introductionmentioning
confidence: 99%
“…Brazilian soils are notably lacking in phosphorus (P), due to the characteristics of the source material and its strong interaction with soil components (Farias et al, 2016). The referred deficiency is found when the efficiency of P recovery, that is, what returns to plant production, is between 5 to 25% of what is applied (Yang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%